Karakteristik Minyak Campuran Red Palm Oil dengan Palm Kernel Olein - Maria Ulfah; Adi Riswanto; Ngatirah Ngatirah (agriTECH, 2016)
Characteristics of oil blends has been produced from red palm oil (RPO) and palm kernel olein (PKOo) with seven ratios with a total of 100, namely A (0:100), B (25:75), C (40:60), D (50:50), E (60:40), F (75:25) and G (100:0) v/v investigated with randomized complete block design. The result showed that different of ratio levels RPO and PKOo have some effects on peroxide value, saponification value, melting point, cloud point and β-carotene content from RPO-PKOo oil blends, but has not effect on free fatty acid content. Higher level of PKOo content on formulas oil blends were decreased of saponification value and melting point, but was increased of cloud point. The best of RPOPKOo oil blends has been obtained at ratio 50:50 (v/v), with 459.52 ppm β-carotene, 1.35 meq/kg peroxide value, 0.09 % free fatty acid, 202.60 saponification value, 24.15 oC melting point and 7.15 oC cloud point. Fatty acids composition were 1.24 % capric acid, 29.00 % lauric acid, 10.09 % miristic acid, 23.10 % palmitic acid, 5.84 linoleic acid, 27.30 % oleic acid and 3.43 % stearic acid.ABSTRAKSifat-sifat minyak campuran yang dihasilkan dari red palm oil (RPO) dan palm kernel olein (PKOo) dengan tujuh tingkat rasio yang totalnya 100, yaitu A (0:100), B (25:75), C (40:60), D (50:50), E (60:40), F (75:25) dan G (100:0) (v/v) dikaji menggunakan rancangan acak lengkap kelompok. Hasil penelitian menunjukkan bahwa rasio RPO:PKOo mempengaruhi angka peroksida, angka penyabunan, melting point, cloud point dan kadar β-karoten dari minyak campuran RPO-PKOo yang dihasilkan, namun tidak mempengaruhi kadar asam lemak bebas. Peningkatan jumlah PKOo yang ditambahkan dalam minyak campuran RPO-PKOo, akan menurunkan angka penyabunan dan melting point, namun akan menaikkan cloud point. Produk minyak campuran RPO-PKOo terbaik diperoleh pada rasio 50:50 (v/v), dengan kadar β-karoten 459,52 ppm, angka peroksida 1,35 meq/kg, asam lemak bebas 0,09 %, angka penyabunan 202,60, melting point 24,15 oC dan cloud point 7,15 oC, serta komposisi asam lemak (kaprat 1,24 %, laurat 29,00 %, miristat 10,09 %, palmitat 23,10 %, linoleat 5,84 %, oleat 27,30 % dan stearat 3,43 %).